How Well Does the ERA5 Reanalysis Capture the Extreme Climate Events Over China? Part II: Extreme Temperature - Xu, Wanling; Lei, Xiangyong; Chen, Shiting; Yu, Tingting; Hu, Zengyun; Zhang, Meng; Jiang, Lizhi; Bao, Ruijuan; Guan, Xiaojun; Ma, Miaomiao; Wei, Jianhui; Gao, Lu; et al. (Frontiers in Environmental Science, 2022)
The fifth-generation atmospheric reanalysis of the European Center for Medium-Range Weather Forecasts (ERA5) is the latest reanalysis product. ERA5 has wider assimilation data sources, greater spatial-temporal resolution, and more advanced four-dimensional variational analysis (4DVAR) than those of other reanalysis products. However, the applicability of ERA5 datasets requires further validation in China. Hence, ERA5 and conventional observation data for 1979–2020 were used to evaluate the credibility of ERA5 in reproducing different extreme temperature indices across the six subregions in China at different timescales. The conclusions are as follows: The original temperature field (mean temperature, maximum temperature, and minimum temperature) can be well reproduced by ERA5 reanalysis over China. ERA5 tends to exhibit more misdetection in the duration of extreme temperature events as compared to that observed with extreme temperature intensity and frequency. Additionally, ERA5 performs best in the summer and worst in the winter. The trend of absolute indices, percentile-based indices, duration indices can be captured by ERA5. Nevertheless, ERA5 failed to capture the tendency of the diurnal temperature range (DTR) over China. Spatially, ERA5 performs well in southeastern China. However, it remains challenging to accurately recreate the extreme temperature events in the Tibetan Plateau by ERA5 reanalysis because of its unique topographical features and rare meteorological observations. The elevation difference between stations and ERA5 affects the accuracy of reanalysis temperature data. The accuracy of ERA5 decreases with the increase in the elevation gap. Furthermore, the latitude position is also a factor affecting the accuracy of ERA5 for capturing extreme temperature indices.